2001
DOI: 10.1385/endo:15:3:305
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels in Diabetic and Nondiabetic Subjects

Abstract: The role of leptin in human pathophysiology elicits considerable interest in view of its potential role as a treatment tool for obesity and other insulin resistant states, like type 2 diabetes mellitus (T2DM). Leptin has been extensively studied in obese humans, and much less so in other pathologic conditions. Leptin level has been reported to correlate with percent body fat mass (%FM), fasting serum insulin (FPI), insulin sensitivity and blood pressure. The aim of this study was to compare the leptin concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
4
24
0
1
Order By: Relevance
“…Abu-Sayeed et al [30] found that lean diabetic patients have shown low leptin levels. These results were also reported by many other researchers [14, 31, 32]. Haffner et al [33] found no differences in the concentration of leptin levels between diabetic and nondiabetic subjects as well as no differences between obese and nonobese subjects.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Abu-Sayeed et al [30] found that lean diabetic patients have shown low leptin levels. These results were also reported by many other researchers [14, 31, 32]. Haffner et al [33] found no differences in the concentration of leptin levels between diabetic and nondiabetic subjects as well as no differences between obese and nonobese subjects.…”
Section: Discussionsupporting
confidence: 87%
“…Ahren et al [42] stressed that leptin levels are increased in patients with high BMI levels (obese). However, other studies argued that leptin levels were reduced in obese and diabetic patients, which attributed to the altered fat distribution [14, 32]. Matsubara et al [43] found that the concentration of serum leptin in women with high levels of BMI was increased compared to those in the middle and/or lower BMI group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 In a cross-sectional study of obese men, multiple regression analysis showed abdominal subcutaneous adipose tissue, glucose disposal rate (GDR) and BMI to explain most of the variability in serum leptin concentration. 74 Tatti et al 75 found that BMI, waist-to-hip ratio, and fasting plasma insulin were significantly related to leptin only in the nondiabetic population, but not in diabetic patients. On the other hand, Wauters et al 76 found that fat mass and gender are the main independent predictors of leptin concentration in type 2 diabetic 118 SOODINI AND HAMDY patients, and that insulin secretion and the degree of insulin resistance contribute significantly to leptin levels.…”
Section: Role Of Leptin In Regulating Appetitementioning
confidence: 99%
“…7 Hyperleptinemia leads also to increased blood pressure via decreased blood flow in the splanchnic bed, 8 hypercoagulation, and increased PAI-1 levels 9 -all these being features of the MS. Leptin levels were also found to be lower in the diabetic population as compared to healthy subjects. 10 Orlistat is a lipase inhibitor leading to nonabsorption of 30% of the fat ingested with food. 11 The landmark study XENDOS (XENical in the prevention of Diabetes in Obese Subjects) has investigated the long-term use of Orlistat for (up to) 4 years in preventing the progression to type 2 diabetes in obese patients with MS. 12 The purpose of the present study was to assess the impact of treatment with Orlistat on serum leptin levels, weight loss, glycemic control, and cardiovascular risk factors involved in the MS.…”
Section: Introductionmentioning
confidence: 99%